2015
DOI: 10.1016/j.ajur.2015.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive transcutaneous electrical stimulation in the treatment of overactive bladder

Abstract: We reviewed the literature on transcutaneous electrical nerve stimulation (TENS) used as a therapy for overactive bladder (OAB) symptoms, with a particular focus on: stimulation site, stimuli parameters, neural structures thought to be targeted, and the clinical and urodynamic outcomes achieved. The majority of studies used sacral or tibial nerve stimulation. The literature suggests that, whilst TENS therapy may have neuromodulation effects, patient are unlikely to benefit to a significant extent from a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 42 publications
0
41
0
1
Order By: Relevance
“…Urological rehabilitation has the neuromodulation as an approach option to reach the detrusor muscle, located in the bladder wall. [2][3][4][5][6] Several studies have shown the use of the electrical stimulation approach for urinary conditions, mainly overactive bladder, neurogenic bladder dysfunction, urinary urge incontinence, and enuresis in adults and pediatrics patients. [3][4][5][6][7][8][9][10][11] However, it is important to highlight that there is a nomenclature conflict regarding one of the detrusor access paths.…”
Section: Introductionmentioning
confidence: 99%
“…Urological rehabilitation has the neuromodulation as an approach option to reach the detrusor muscle, located in the bladder wall. [2][3][4][5][6] Several studies have shown the use of the electrical stimulation approach for urinary conditions, mainly overactive bladder, neurogenic bladder dysfunction, urinary urge incontinence, and enuresis in adults and pediatrics patients. [3][4][5][6][7][8][9][10][11] However, it is important to highlight that there is a nomenclature conflict regarding one of the detrusor access paths.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this, the present protocol may corroborate with the literature on the effect of transcutaneous electrostimulation on urgency at the tibial nerve level and the parasacral region. Slovak et al [14] in their study conclude that there is limited evidence of stimulation in other locations, the most logical approach to be used in transcutaneous electrical stimulation techniques seems to be stimulation in the sacral or tibial region, since they directly or indirectly target the medullar root S3.…”
Section: Discussionmentioning
confidence: 99%
“…Electrical stimulation is used as a resource for UUI treatment in the physiotherapist's clinical practice [11,12]. Transcutaneous tibial nerve stimulation (TTNS) aims to facilitate inhibition of the detrusor muscle [13] by means of electrostimulation in the path of the tibial nerve [14]. The tibial nerve is a mixed nerve [15], that originates in the L5-S3 nerve roots, which are the same roots that innervate the parasympathetic pathway of the bladder (S2-S4) [14,16], thus, it is suggested that direct stimulation of the tibial nerve could inhibit the S2-S3 afferents, thereby decreasing detrusor hyperactivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…153,154 Percutaneous tibial NS (PTNS) and transcutaneous tibial NS are functionally comparable methods of stimulating the posterior tibial nerve at the ankle. 155,156 The techniques are similar to conventional TENS in the use of perceptible nonpainful stimulation, although the frequency is 20 Hz. The posterior tibial nerve is a mixed nerve originating from segments L4-S3, which overlap with the parasympathetic innervation to the bladder involving segments S2-S4.…”
Section: Remote Effects Of Nerve Stimulation In Nonpain Applicationsmentioning
confidence: 99%